FAITH IN FOREST: PERSEPSI GENERASI Z TERHADAP ECOTHEOLOGY DAN KEPEDULIAN LINGKUNGAN DALAM KONTEKS KEAGAMAAN - Salmah, Salmah; Putri, Shella Aulia; Surawan, Surawan (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
The global environmental crisis, marked by climate change, deforestation, pollution, and the increasing frequency of natural disasters, requires stronger ecological awareness, particularly among younger generations. Generation Z, as digital natives, holds great potential to become agents of change in integrating religious values with ecological concern. This study aims to analyze Generation Z’s perception of ecotheology and environmental awareness in religious contexts. The method employed is a literature review with content analysis of eight scholarly articles discussing ecotheology, disaster theology, youth movements, Islamic education, and global spirituality perspectives. The findings reveal that Generation Z tends to adopt a more critical perspective on environmental issues compared to previous generations and is able to connect faith-based values with ecological practices through social movements, education, and digital platforms. The study concludes that Generation Z plays a crucial role in shaping ecotheological narratives that are both religious and adaptive to modern challenges, thereby fostering a Muslim generation that is religious, ecological, and prepared to face global environmental crises.